2020
DOI: 10.3390/s20205925
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Measurements during Magnetic Pulse Welding Using CMR-B-Scalar Sensors

Abstract: The possibility of applying CMR-B-scalar sensors made from thin manganite films exhibiting the colossal magnetoresistance effect as a fast-nondestructive method for the evaluation of the quality of the magnetic pulse welding (MPW) process is investigated in this paper. This method based on magnetic field magnitude measurements in the vicinity of the tools and joining parts was tested during the electromagnetic compression and MPW of an aluminum flyer tube with a steel parent. The testing setup used for the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The signal is synchronized and recorded simultaneously by recording channels. The magnetic field measurement system was used for measurements of magnetic field distribution and diffusion during operation of electromagnetic launchers [ 18 , 89 , 90 ], highly inhomogeneous transient fields in a coil gun [ 91 ], field distribution in nondestructive pulsed magnets [ 92 ], welding quality control in magnetic forming and welding systems [ 93 ]. Despite the fact that the resistance of manganite film, which is a basic element of the sensor, is dependent on ambient temperature, the CMR-B-scalar sensors can be successfully calibrated in advance in a wide range of temperatures (see Figure 13 b) and the data are stored in the software of the system what allows simultaneous conversion of the measured signal (voltage) to magnetic field values [ 10 ].…”
Section: Colossal Magnetoresistance Materialsmentioning
confidence: 99%
“…The signal is synchronized and recorded simultaneously by recording channels. The magnetic field measurement system was used for measurements of magnetic field distribution and diffusion during operation of electromagnetic launchers [ 18 , 89 , 90 ], highly inhomogeneous transient fields in a coil gun [ 91 ], field distribution in nondestructive pulsed magnets [ 92 ], welding quality control in magnetic forming and welding systems [ 93 ]. Despite the fact that the resistance of manganite film, which is a basic element of the sensor, is dependent on ambient temperature, the CMR-B-scalar sensors can be successfully calibrated in advance in a wide range of temperatures (see Figure 13 b) and the data are stored in the software of the system what allows simultaneous conversion of the measured signal (voltage) to magnetic field values [ 10 ].…”
Section: Colossal Magnetoresistance Materialsmentioning
confidence: 99%
“…Experimental measurement of the impact velocity in MPW was largely conducted using optical methods, particularly with the use of a photonic Doppler velocimeter (PDV) [44,45]. In their previous work, the authors validated the FEM employed in this study by comparing the simulated impact velocity with the experimental impact velocity measured using PDV for various process conditions.…”
Section: Experimental Corroboration Of Fem Observationsmentioning
confidence: 99%
“…It was demonstrated that nanostructured La 1−x Sr x MnO 3 (La-Sr-Mn-O, LSMO) manganite films can be used for the development of magnetic sensors, which are capable of measuring the magnitude of pulsed magnetic fields in very small volumes (so-called CMR-B scalar sensors) up to very high magnetic fields [8,14]. Such sensors were used for the magnetic field measurement during electromagnetic acceleration in railguns and superconducting systems [15,16], the magnetic field distribution in non-destructive pulsed-field magnets [17], and evaluation of welding quality during magnetic welding of metals [18]. The possibility to tune temperature and magnetic field ranges of operation of CMR sensors by changing deposition temperature and film thickness was demonstrated [19].…”
Section: Introductionmentioning
confidence: 99%